A comparative study between Malaysian law and law in United Kingdom: cruelty against cats / Ahmad Muhaimin Abdul Aziz …[et al.] - Abdul Aziz, Ahmad Muhaimin; Mohd Yusof, Amelda; Mohd Noor, Anith Amyrah; Aris, Hrrison (2010)
Problems occurred on cats are normally abused cats and excessive stray cats on the streets. This research contains the differences of Malaysian law and United Kingdom law in dealing with cruelty against cats. Malaysian laws on cats need to be renewed in order to be able to fit in the new era. The over-population of stray cats and massive abused cats in our country is not to be taken lightly. This phenomenon reflects the negative attitude of our citizen on the relationship between human and animals. The local laws need to step up and enforce its law accordingly to make the law an effective law. Here, the comparison on Animals Act 1953 (Act 647) and Animal Welfare Act 2006 in United Kingdom is studied. Interviews are conducted to the government bodies and non-governmental organizations. The result of the interviews are analysed to seek on the major differences of these laws. Accordingly, these analysis are recorded and conclusions are made. Reports on the interviews are made. The reports shows there are certainly some areas in the local laws that need amendments. Therefore, amendments in terms of sufficiency of the punishment, protection and enforcement of the local law are necessary.